Translating falls prevention knowledge to community-dwelling older PLWD: A mixed-method systematic review - Meyer, C.; Hill, S.; Dow, B.; Synnot, A.; Hill, Keith (Gerontological Society of America, 2015)
© The Author 2013. Published by Oxford University Press on behalf of The Gerontological Society of America. Purpose of the Study: Falls prevention evidence is strong, but little is known about uptake of strategies for people living with dementia (PLWD). This mixed-method systematic review aimed to integrate evidence of falls prevention efficacy with views/experiences of PLWD. Design and Methods: Eight electronic databases were searched. Inclusion criteria included quantitative or qualitative studies examining knowledge translation of falls prevention strategies in community-dwelling PLWD and/or their caregiver. Study quality was assessed, and findings are narratively described. Results: Six quantitative and five qualitative studies were included. Study quality was mixed. Quantitative studies showed limited evidence of effectiveness on reduction in falls risk, falls and hospitalization rates, nursing home admission, decline in activities of daily living, and adherence to strategies. Qualitative themes showed inclusion of caregiver and health professionals as key to program success, but many factors influence participation. Implications: Synthesizing the findings generated a new understanding of falls prevention for this high-risk group. A focus upon health professional and caregiver involvement and accommodation of individual preferences may result in increased engagement with falls prevention strategies.